Memaknai Pendidikan Dalam Hadits Nabi - Subri Subri (IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2017)
One of the sources of Islamic law are important in the formation of the law after the Qur'an is al-Hadith. Besides that, the hadeeth also has another function, namely as explanatory of what is contained in the Qur'an that are global. Elaborate or give an example implementation. And already we understand together, that when the Prophet died, he did not leave anything for his people except al-Quran and al-Hadith. With two pengangan source of life, humans would survive in the world and in the hereafter for lanterns used throughout his life. To understand both needed a tool in the form of science that in reviewing and assessing the two are not misreading and interpretation. And the knowledge gained through the educational process.